Continuum modeling for lithium storage inside nanotubes - Alsaud, Huda; Alshehri, Mansoor H. (Frontiers in Physics, 2023)
Lithium storage and capture are of particular importance for the development of new technology in electric vehicles and portable electronics. Nanotubes are among many porous nanomaterials offered as potential candidates for Lithium storage. In this paper, we adopt a continuum approach together with Lennard-Jones function to determine the minimum interaction energies for lithium atoms in boron nitride and carbon nanotubes. By minimizing the interaction energies we may obtain the preferred type and size of the nanotubes to encapsulate the lithium atoms. The results observe that the boron nitride and carbon nanotubes are attractive candidates for lithium atom encapsulating, and the optimal nanotube to enclose the lithium is the boron nitride nanotube with radius equal to 3.4 Å corresponding (5,5) armchair nanotubes and (9, 0) zigzag nanotubes, at the lowest minimum energy is occurred. The present computations observed that both nanotubes are promising candidates for lithium intercalation materials suitable for battery applications.